P-67 Advance care planning in a UK hospice: the experiences of trained volunteers. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Jones, Penny; Heaps, Kate; Rattigan, Carla; Maran, Marks Diane
Abstract : Introduction: Advance Care Planning (ACP) enables better planning/provision of care for people nearing the end-of-life so that they can live and die in the place/manner of their choosing (Gold Standards Framework 2014). Greenwich and Bexley Community Hospice launched a project to enable people with life-limiting illnesses to develop an ACP through working with a trained volunteer. Aims: To recruit/train volunteers to visit people with life-limiting illness to help them articulate their end-of-life care wishes. To evaluate the volunteers' experiences. This poster presentation reports on the results of this evaluation research. Methods: Research approach : Mixed-method case study with a framework devised by Marks-Maran (2014) evaluating: Volunteers' engagement/value of their role Impact on the volunteers Sustainability of the role Topics discussed with service users. Ethical approval : gained from Greenwich University Researcher: an honorary research fellow from that Greenwich University Data collection: mixed-method questionnaire Sample : 19 questionnaires sent; 10 returned (response rate = 53%) Results: The strongest areas of engagement in/value were: supporting clients to discuss their wishes, helping clients to be satisfied with their ACP and enabling clients to share their anxieties. From the responses received the volunteers felt that the training programme prepared them well and the support they received was felt to be valued. The volunteer role was viewed positively by all respondents and described as being "enriching" and "personally satisfying." For some volunteers, it helped develop new skills. With the greatest impact was felt to be helping the carers feel less anxious and helping clients to communicate their wishes. All respondents would recommend others to become volunteers and recommend the programme should continue. Topics clients wanted to discuss ranged from: funeral arrangements; their diagnosis; family dynamics and what information is available about future support. Conclusion: The volunteer ACP project was successful. More volunteers are being recruited and trained and some small changes to the training programme have been made from volunteers' suggestions